Back Cover: Preclinical pharmacokinetics of trigonelline using ultra‐performance liquid chromatography–tandem mass spectrometry and pharmacological studies targeting type 2 diabetes. Issue 4 (2nd April 2021) - Wadhwa, Geetika; Krishna, Kowthavarapu Venkata; Taliyan, Rajeev; Tandon, Neeraj; Yadav, Satyapal Singh; Banerjee, Dipankar; Narwaria, Avinash; Katiyar, Chandra Kant; Dubey, Sunil Kumar
Abstract : DOI: 10.1002/sscp.202000118 The cover picture shows, Trigonelline (Tr) a quaternary base alkaloid, which acts by affecting β‐cell regeneration and insulin secretion. Tr lowers the blood glucose and lipid levels due to which it is used in the treatment of co‐morbid diseases. Herein, we have aimed to develop a bioanalytical method for estimation of Tr using UPLC‐MS/MS and explore the pharmacokinetic profile. The anti‐diabetic, antilipidemic efficacy studies were also conducted in the high‐fat diet‐induced streptozotocin‐diabetic rat. The experimental results suggest that Tr follow the two compartmental pharmacokinetic model. In addition, Tr exhibited a significant anti‐hyperglycemic and antihyperlipidemic efficacy in high‐fat diet‐induced streptozotocin induced diabetic rats.